2020
DOI: 10.1016/j.scitotenv.2019.134571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding natural sounds to urban noises on the perceived loudness of noise and soundscape quality

Abstract: Introducing pleasant natural sounds to mask urban noises is an important soundscape design strategy to improve acoustic comfort. This study investigates the effects of signal-to-noise ratio (SNR) between natural sounds (signal) and the target noises (noise) and their temporal characteristics on the perceived loudness of noise (PLN) and overall soundscape quality (OSQ) through a laboratory experiment. Two types of urban noise sources (hydraulic breaker and traffic noises) were set to A-weighted equivalent sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 46 publications
7
52
1
Order By: Relevance
“…Previous research into the soundscapes of underground business streets found that, as SPL increases, the acoustic comfort index varies in a parabola shape [45]. Recent paper indicated that the overall effect of nature sound on soundscape perception increases as the signal-to-noise ratio becomes larger, and begins to decrease slightly afterwards [46]. Theses findings are in line with the results in this research.…”
supporting
confidence: 91%
“…Previous research into the soundscapes of underground business streets found that, as SPL increases, the acoustic comfort index varies in a parabola shape [45]. Recent paper indicated that the overall effect of nature sound on soundscape perception increases as the signal-to-noise ratio becomes larger, and begins to decrease slightly afterwards [46]. Theses findings are in line with the results in this research.…”
supporting
confidence: 91%
“…Introducing natural sounds into the sound landscape (e.g., water noise, birdsong) to mask urban sounds can significantly improve their acoustic comfort. This approach should be an essential strategy for designing green areas in urban areas to improve the well-being of those residing there [60][61][62][63]. Also, the authors [64,65] indicate that landscape architects should, in their design work, take into account such aspects as the acoustic properties of materials, the possibility of masking, or introducing elements of small architecture with the functions of "white noise."…”
Section: Discussionmentioning
confidence: 99%
“…Calibrating audio tracks to fixed or user-specified (equivalent continuous sound pressure level) values when played back over headphones is a perennial concern for many studies in psychoacoustics and soundscapes. For example, laboratory studies may seek to fix a track at a particular in order to remove the as a possible confounding variable while investigating the effects of a different variable [1 , 2] , or may require audio tracks calibrated to different values in order to study the effect of on a separate dependent variable [3] . It has been found that the that a given audio stimulus is presented over headphones affects its subjective perception [3] , and that reproduction system quality affects the ecological validity of the results of laboratory experiments [4] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, laboratory studies may seek to fix a track at a particular in order to remove the as a possible confounding variable while investigating the effects of a different variable [1 , 2] , or may require audio tracks calibrated to different values in order to study the effect of on a separate dependent variable [3] . It has been found that the that a given audio stimulus is presented over headphones affects its subjective perception [3] , and that reproduction system quality affects the ecological validity of the results of laboratory experiments [4] . Hence, accurate and reliable calibrations need to be performed to ensure the consistency and replicability of experiments that depend on human judgement and perceptions of sound.…”
Section: Introductionmentioning
confidence: 99%